2009
DOI: 10.2528/pier09060403
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Screen With Magnetically Controlled Attenuation

Abstract: Abstract-The effect of magnetic bias on dielectric spectra of composite sheets filled with Fe or Co-based microwires is studied experimentally and via simulation. The permittivity is measured using a free-space technique within the frequency band from 6 to 12 GHz. The bias is applied either parallel or perpendicular to the microwave electric field; the bias strength varies from 0 to 2.5 kOe. The composites with Fe-based wires reveal a single region of bias dependent permittivity under bias about 800-1000 Oe. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 24 publications
1
20
0
Order By: Relevance
“…For instance, in the case of a = 0.4d and h = 2.5d, the attenuation coefficient of the spoof SPPs is 23 m −1 for f = 0.6 THz, and it increases up to 59 m −1 for f = 0.8 THz and 134 for f = 1 THz, respectively. Compared to a metal THz waveguide described in [44], the corrugated semiconductor surface exhibits relatively high loss for guiding THz wave. The mentioned outcome appears due to the fact that the permittivity of metal is smaller than that of silicon.…”
Section: Example: Simentioning
confidence: 98%
“…For instance, in the case of a = 0.4d and h = 2.5d, the attenuation coefficient of the spoof SPPs is 23 m −1 for f = 0.6 THz, and it increases up to 59 m −1 for f = 0.8 THz and 134 for f = 1 THz, respectively. Compared to a metal THz waveguide described in [44], the corrugated semiconductor surface exhibits relatively high loss for guiding THz wave. The mentioned outcome appears due to the fact that the permittivity of metal is smaller than that of silicon.…”
Section: Example: Simentioning
confidence: 98%
“…Among them, ferromagnetic wires have been proposed for the design of electromagnetic absorbers, [5][6][7] transmission control screens, 8,9 electromagnetic shields, 10 artificial surfaces, 11 and noninvasive testing devices. 12 In addition, ferromagnetic wires are used as the elementary inclusion of artificial electromagnetic materials, such as artificial dielectrics with magnetically controllable permittivity, [13][14][15][16] and magnetic materials with adjustable permeability.…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, microwave absorption, electromagnetic compatibility, and non-destructive testing applications were also developed in the microwave and millimetre-wave applications. [2][3][4][5][6] They are desirable elements for configurating microwave tuneable devices through indirect field tuning; and a few recent studies have demonstrated such feature in microwirebased composite materials. 5,7 At gigahertz frequency range, microwires behave collectively like dipoles when they interact with an incident microwave field.…”
mentioning
confidence: 99%
“…6,8 Several studies have been performed on the influence of a magnetic field on the effective scattering parameters and the permittivity of wire composites containing periodic arrays of ferromagnetic wires. 6,[9][10][11] However, the above mentioned studies have not been extended to composite materials obtained by randomly dispersing microwires in a polymer matrix. The short wire inclusion can be considered as elementary scatterers when the electromagnetic wave propagates in the composite and induces an electric dipole moment in each inclusion.…”
mentioning
confidence: 99%
See 1 more Smart Citation